(untitled) - Bowles, Dorothy A. (Belmont, CA, 2004)
The edition also expands and updates material on journalism ethics, including new discussion about media credibility, media convergence, online ethics and recent incidences of ethical lapses by journalists at large media organizations.
Keywords: Journalism,Editing; Editing